Black Madonna A Womanist Look at Mary of Nazareth. - Lee, Courtney Hall. (Eugene : Wipf and Stock Publishers, 2017)
The figure of the Virgin Mary comes loaded with baggage and preconceptions. She is usually depicted as the perfect, obedient, and highly esteemed woman, much like the Victorian notion of the ""angel in the house."" For many black women, nothing could be more inaccessible. This book considers the relationship between African American women and Mary of Nazareth. After examining the history of black American motherhood during slavery and beyond, this book then gives an overview of the existing views of Mary in both the church and the academy. Lee then brings African American women and Mary togeth.
Pages:1 to 25; Pages:26 to 50; Pages:51 to 75; Pages:76 to 100; Pages:101 to 125; Pages:126 to 150
Description based upon print version of record.
Added to collection customer.56279.3 - Master record variable field(s) change: 072
Keywords: Mary, -- Blessed Virgin, Saint -- Theology; Mary, -- Blessed Virgin, Saint; Theology of the Blessed Virgin Mary; RELIGION / Christian Theology / Christology; Electronic books